Tungsten doped diamond shells for record neutron yield inertial confinement fusion experiments at the National Ignition Facility. (1st January 2023) - Braun, T.; Kucheyev, S.O.; Shin, S.J.; Wang, Y.M.; Ye, J.; Teslich Jr, N.E.; Saw, C.K.; Bober, D.B.; Sedillo, E.M.; Rice, N.G.; Sequoia, K.; Huang, H.; et al.
Abstract: We report on fabrication and characterization of layered, tungsten doped, spherical about 2 mm diameter microcrystalline diamond ablator shells for inertial confinement fusion (ICF) experiments at the National Ignition Facility. As previously reported, diamond ICF ablator shells can be fabricated by chemical vapor deposition (CVD) on solid spherical silicon mandrels using an ellipsoidal microwave plasma reactor. In the present work, we further developed these ablator shells by embedding a W -doped diamond layer sandwiched between two undoped diamond regions. W incorporation in diamond was achieved by adding tungsten hexacarbonyl to the CH4 /H2 CVD feed gas. We observe that the W doping concentration decreases with increasing deposition rate which, in turn, is controlled by adjusting the total gas pressure. Cross sectional microstructural analysis reveals sharp interfaces between doped and undoped regions of the diamond shell and uniform W distribution with concentrations up to about 0.3 at.%. At higher W concentrations (>0.3 at.%) formation of tungsten carbide precipitates is observed. Using a 3‐shock 1.6 MJ laser pulse, the targets described in this work produced the first laser driven implosion to break the 1 × 10 16 neutron yield barrier, followed by experiments (described in future publications) with similar targets and slightly more laser energy producing yields as high as 4 × 10 17 .